Treatment of simulated refinery based sulfidic spent caustic using photo-fenton oxidation - Sayid Abdullah, Sharifah Hanis Yasmin (2012)
Sulfidic spent caustic is the spent solution produced as a result of scrubbing process in a refinery operation. The hazardous and toxicity nature of sulfidic spent caustic indicated that this waste must be thoroughly treated before being dumped into the water sources. Since photo-Fenton oxidation has been widely applied for treatment of various types of wastewater, this study was performed to investigate the applicability of photo-Fenton oxidation for treating sulfidic spent caustic produced by refinery operation. The photo-Fenton oxidation of sulfidic spent caustic was carried out in a lab scale photo-reactor with working volume of 250 mL for 40 minutes reaction time. By using Response Surface Methodology (RSM), the optimal conditions for photo-Fenton oxidation process were found to be at Fe/H2O2 and H2O2/COD dosage ratio of 0.07 and 1.84 respectively. It was also found that photo-Fenton process exhibited higher degradation efficiency up to 96% chemical oxygen demand (COD) removal as compared to 83% in conventional Fenton. Higher reaction rate constant was obtained in photo- Fenton process (0.251 min-1) as compared to Fenton process (0.169 min-1). Furthermore, the degradation route of sulfidic spent caustic oxidation was established in this study where nearly all the sulfide compounds in the solution were degraded into sulfate endproducts. The catalyst recycling study confirmed that the formed ferric sludge can be recycled back into the system as a catalyst up to six treatment cycles. In conclusion, photo-Fenton oxidation process was found to be an effective treatment option for the remediation of sulfidic spent caustic wastewater.